Polimorfisme Warna dan Karakter Morfologi Kumbang Rynchophorus spp. yang Berasosiasi Pada Tanaman Sagu di Maluku - Sanuari, Renny V Y; Rumthe, Ria Y; Sahetappy, Betty (Universitas Pattimura, 2024)
The objective of this research was to determine the polymorphism and morphometric patterns of sago beetles that live on sago plants. This research used sago trees that had been cut down and pheromone traps by taking samples of sago beetles trapped in Rutong Village, South Leitimur District, Ambon Municipality. A descriptive method was used by identifying sago beetles through observing color polymorphism and morphometric characters. The results showed that in Rutong villagee there were 2 types of species found based on the shape of the color pattern, namely Rynchophorus bilineatus which has 3 color patterns on the pronotal part which characterizes R. bilineatus, namely: 1) the pronotal is dark black without any red color, 2) the pronotal black with a flat red pattern on the pronotal apex, 3) a dotted red pattern running along the middle of the pronotal and Rynchophorus vulneratus has 1 solid red pattern running along the pronotal. The morphometric characteristics shown in the body length of R. bilineatus is 30.05-30.55 mm and this is smaller than the body length of R. vulneratus, which is 32.32-37.35 mm.